How psychology can help limit climate change - Nielsen, Kristian S; Clayton, Susan; Stern, Paul C; Dietz, Thomas; Capstick, Stuart; Whitmarsh, Lorraine (The American psychologist, 2021)
The Intergovernmental Panel on Climate Change has encouraged psychologists to become part of the integrated scientific effort to support the achievement of climate change targets such as keeping within 1.5°C or 2°C of global warming. To date, the typical psychological approach has been to demonstrate that specific concepts and theories can predict behaviors that contribute to or mitigate climate change. Psychologists need to go further and, in particular, show that integrating psychological concepts into feasible interventions can reduce greenhouse gas emissions far more than would be achieved without such integration. While critiquing some aspects of current approaches, we describe psychological research that is pointing the way by distinguishing different types of behavior, acknowledging sociocultural context, and collaborating with other disciplines. Engaging this challenge offers psychologists new opportunities for promoting mitigation, advancing psychological understanding, and developing better interdisciplinary interactions. (PsycInfo Database Record (c) 2021 APA, all rights reserved).